1997
DOI: 10.1021/ma9708757
|View full text |Cite
|
Sign up to set email alerts
|

2D Exchange NMR Investigation of the α-Relaxation in Poly(ethyl methacrylate) as Compared to Poly(methyl methacrylate)

Abstract: The main chain dynamics of amorphous poly(ethyl methacrylate) (PEMA) and poly(methyl methacrylate) (PMMA) below and above their respective glass transition temperatures T g are analyzed by two-dimensional solid-state exchange 2H NMR spectroscopy. In both polymers, a restricted mobility of the polymer backbone is already present in the glassy state, as is directly demonstrated and quantified using samples deuterated at the methyl and methylene moieties of the polymer main chain. The unusual main chain mobility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
95
0
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 33 publications
9
95
0
6
Order By: Relevance
“…7,8 Furthermore, other subglass and glass relaxation processes in PMMA have been studied for a long time mainly by dynamic mechanical analysis, dielectric spectroscopy, and advanced NMR spectroscopy. [9][10][11][12][13][14][15][16][17] Especially in the temperature range close to and above the glass-transition temperature (T g ≈ 400 K), PMMA exhibits a complicated dynamics. A complexsand likely cooperativessecondaryrelaxation has been reported, which masks the pure R-process when techniques such as mechanical or dielectric spectroscopy (e.g., ref 13) are used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Furthermore, other subglass and glass relaxation processes in PMMA have been studied for a long time mainly by dynamic mechanical analysis, dielectric spectroscopy, and advanced NMR spectroscopy. [9][10][11][12][13][14][15][16][17] Especially in the temperature range close to and above the glass-transition temperature (T g ≈ 400 K), PMMA exhibits a complicated dynamics. A complexsand likely cooperativessecondaryrelaxation has been reported, which masks the pure R-process when techniques such as mechanical or dielectric spectroscopy (e.g., ref 13) are used.…”
Section: Introductionmentioning
confidence: 99%
“…11 The corresponding results led to the conclusion that this process relates to π-flips of the carboxyl side group which are coupled with rotational readjustments of the local chain axis with amplitude of about (20°(rocking motion). Moreover, by using two-dimensional NMR spectroscopy on PMMA, Kuebler et al 12 reported that the -relaxation largely influences the R-relaxation time scale leading to a high mobility of the main chain. In agreement with these findings, Soldera et al 18 found a correlation between the dihedral angle motions of the backbone and the side groups by using molecular simulations.…”
Section: Introductionmentioning
confidence: 99%
“…10 presents the coupling of α and β processes for PMMA. PMMA and PEMA studied by NMR [71,72] reveal that the β process at temperatures below but near T g is not strictly local but rather consists of π flips of the carboxyl group accompanied by restricted rearrangements of the main chain. In PMMA the side group reorients rapidly and couples with the time scale of the α process.…”
Section: αβ Splittingmentioning
confidence: 99%
“…Among the poly(n-alkyl methacrylate)s, the most studied ones are PMMA (poly-(methyl methacrylate)) [64,[68][69][70][71][72], PEMA (poly(ethyl methacrylate)) [64,[66][67][69][70][71][72][73][74] and PnBMA (poly(n-butyl methacrylate)) [64,[69][70][72][73][74], mainly by DRS and NMR. The first studies by dielectric relaxation spectroscopy of poly(n-alkyl methacrylate)s (revised in ref.…”
Section: αβ Splittingmentioning
confidence: 99%
“…Vários estudos foram realizados nos poli(metacrilatos de n-alquila), utilizando as técnicas de relaxação mecânica e dielétrica, 1,2,6-9 RMN, [11][12][13][14][15][16][17][18][19][21][22][23][24][25][26] infra-vermelho, espalhamento de nêutrons e raios-x, 2,10 fornecendo informações sobre o seu processo de relaxação, a sua estrutura e a sua dinâmica molecular. Hoje em dia sabe-se que os poli(metacrilatos de n-alquila) possuem várias formas de relaxação estrutural, entre elas a relaxação α que acontece na região da temperatura de transição vítrea T g e a relaxação β que acontece a temperaturas abaixo da T g , e outras relaxações que ocorrem a mais baixas temperaturas.…”
Section: 21-26unclassified